Ecologia política, infraestrutura e ambiente: um olhar sobre a atuação de coletivos comunitários em territórios periféricos vulneráveis - Cândido, Maria Eduarda (2024)
This research aims to examine the dynamics of mobilization and participation of community collectives that work in areas of social and environmental vulnerability located in the peripheries of large cities. For this, the case study of the environmental performance of the DLIS Network was carried out, a collective formed by more than thirty institutions that operates in the Grande Bom Jardim, a territory made up of five neighborhoods considered among the most vulnerable in the city of Fortaleza/Brazil. The hypothesis raised is that the technical-political performance of the DLIS Network is reflected in material gains for the urban environment, through the design of solutions more appropriate to the local ecosystem, especially sanitation works, demarcation of protected areas and requalification works in areas of environmental interest. The research methodology uses the tools of bibliographic review, document analysis, field observation and semi-structured interviews. In this analytical context, we seek to review the global conjuncture of social and environmental degradation of cities, highlighting the conceptual categories of Political Ecology, Insurgent Planning and Green Infrastructure. The study also discussed ways to incorporate knowledge of the practices of popular movements in the guidelines of public policies related to the urban environment. The results achieved in the research indicate that the experience accumulated in community actions makes an important contribution to the readjustment of more socially just urban policies and projects. In this scenario, the following are highlighted: a more sensitive understanding of the political and productive context; the pedagogical action for the formulation of spaces of co-creation between the different actors; the conjunction of technical knowledge with popular knowledge; the understanding of nature in an integrated way, considering the structuring and symbolic aspects; a better assimilation of environmental problems arising from social inequalities.